Parvovirus B19-Induced Constellation of Acute Renal Failure, Elevated Aminotransferases and Congestive Heart Failure - Iain W McAuley; Farshad Sepandj; Walter Schlech (Canadian Journal of Infectious Diseases)
This report details a case of acute renal failure and elevated aminotransferases with subsequent development of congestive heart failure in a patient with history of exposure to parvovirus B19 and serological evidence of acute infection with this agent. This constellation of organ involvement has not been previously reported in the literature.